Protective Role of Natural and Semi-Synthetic Tocopherols on TNFα-Induced ROS Production and ICAM-1 and Cl-2 Expression in HT29 Intestinal Epithelial Cells - Vladana Domazetovic; Irene Falsetti; Caterina Viglianisi; Kristian Vasa; Cinzia Aurilia; Maria Stio; Stefano Menichetti; Teresa Iantomasi (MDPI AG, 2021)
Vitamin E, a fat-soluble compound, possesses both antioxidant and non-antioxidant properties. In this study we evaluated, in intestinal HT29 cells, the role of natural tocopherols, α-Toc and δ-Toc, and two semi-synthetic derivatives, namely bis-δ-Toc sulfide (δ-Toc)2S and bis-δ-Toc disulfide (δ-Toc)2S2, on TNFα-induced oxidative stress, and intercellular adhesion molecule-1 (ICAM-1) and claudin-2 (Cl-2) expression. The role of tocopherols was compared to that of N-acetylcysteine (NAC), an antioxidant precursor of glutathione synthesis. The results show that all tocopherol containing derivatives used, prevented TNFα-induced oxidative stress and the increase of ICAM-1 and Cl-2 expression, and that (δ-Toc)2S and (δ-Toc)2S2 are more effective than δ-Toc and α-Toc. The beneficial effects demonstrated were due to tocopherol antioxidant properties, but suppression of TNFα-induced Cl-2 expression seems not only to be related with antioxidant ability. Indeed, while ICAM-1 expression is strongly related to the intracellular redox state, Cl-2 expression is TNFα-up-regulated by both redox and non-redox dependent mechanisms. Since ICAM-1 and Cl-2 increase intestinal bowel diseases, and cause excessive recruitment of immune cells and alteration of the intestinal barrier, natural and, above all, semi-synthetic tocopherols may have a potential role as a therapeutic support against intestinal chronic inflammation, in which TNFα represents an important proinflammatory mediator.